Consequences of prefrontal tDCS on inhibitory control and reactive aggression. Issue 1 (24th November 2020) - Weidler, Carmen; Habel, Ute; Wallheinke, Paul; Wagels, Lisa; Hofhansel, Lena; Ling, Shichun; Blendy, Julie A; Clemens, Benjamin
Abstract: Increased aggression and impulsivity represent a key component of several psychiatric disorders, including substance use disorder, which is often associated with deficient prefrontal brain activation. Thus, innovative tools to increase cognitive control are highly warranted. The current study investigates the potential of transcranial direct current stimulation (tDCS), a tool to modulate cortical activation and to increase cognitive control in individuals with a high potential for impulsive and aggressive behavior. In a double-blind, sham-controlled study, we applied anodal tDCS over the right dorsolateral prefrontal cortex in an all-male sample of alcohol-dependent patients (AD), tobacco users (TU) and healthy controls (HC), who completed the Taylor Aggression Paradigm and Stop Signal Reaction Time Task twice. While there were no observable effects of tDCS in controls, the results revealed altered aggressive behavior in AD following active stimulation. Specifically, these individuals did not show the standard increase in aggression over time seen in the other groups. Furthermore, improved response inhibition was found in AD and TU following active but not sham stimulation. Our study demonstrates that prefrontal tDCS improves our laboratory measure of impulse control in at-risk groups, illustrating the importance of sample characteristics such as nicotine intake and personality traits for understanding the effects of brain stimulation.